Efficient microwave-assisted Suzuki–Miyaura cross-coupling reaction of 3-bromo pyrazolo[1, 5-a]pyrimidin-5(4H)-one: towards a new access to 3, 5-diarylated 7-(trifluoromethyl)pyrazolo[1, 5-a]pyrimidine derivatives. Issue 3 (4th January 2021) - Jismy, Badr; Guillaumet, Gérald; Akssira, Mohamed; Tikad, Abdellatif; Abarbri, Mohamed
Abstract : A convenient and efficient synthetic route to C3-arylated 7-trifluoromethylpyrazolo[1, 5- a ]pyrimidin-5-one derivatives has been reported starting from 3-bromo-7-(trifluoromethyl)pyrazolo[1, 5- a ]pyrimidin-5-one through a Suzuki–Miyaura cross-coupling reaction. Abstract : A convenient and efficient synthetic route to C3-arylated 7-trifluoromethylpyrazolo[1, 5- a ]pyrimidin-5-one derivatives has been reported starting from 3-bromo-7-(trifluoromethyl)pyrazolo[1, 5- a ]pyrimidin-5-one through a Suzuki–Miyaura cross-coupling reaction. The arylation (heteroarylation) strategy can be performed using a wide variety of aryl and heteroaryl boronic acids and requiring a tandem catalyst XPhosPdG2/XPhos to avoid the debromination reaction. These optimized conditions were successfully extended to the synthesis of 7-, 8- and 9-arylated pyrimido[1, 2- b ]indazol-2-ones from their corresponding brominated starting materials. Furthermore, the second C-5 arylation of C3-arylated pyrazolo[1, 5- a ]pyrimidin-5-ones was achieved under standard Suzuki–Miyaura cross-coupling conditions, after activating the C–O bond of the lactam function with PyBroP, giving access to a small library of 3, 5-diarylated 7-(trifluoromethyl)pyrazolo[1, 5- a ]pyrimidines in good to excellent yields. The interest of this approach has been highlighted by the synthesis of a known anti-inflammatory agent. Additionally, a preliminary biological evaluation has revealed that a number of derivatives display micromolar IC50 values against monoamine oxidase B, an important target in the field of neurodegenerative disorders.